The Existence of Marriage Guardians in Tunisia`s Islamic Family Law - Syarifah Arabiyah (International Journal Labs, 2025)
The issue of marriage guardianship (wali) has become a significant topic in the reform of Islamic family law across Muslim-majority countries, including Tunisia. While most classical scholars consider a marriage guardian essential for a valid marriage, Tunisia allows adult women to contract marriage independently. This study aims to examine the legal status of marriage guardianship in Tunisia’s Islamic family law and compare it with Indonesia’s legal framework. The research uses a normative juridical method, a library research approach, and comparative analysis. The findings reveal that although Tunisia predominantly follows the Maliki school, it adopts the Hanafi opinion in granting mature women the right to marry without a guardian, as formalized in Article 3 of Law No. 39 of 2010. The implication is that Tunisia’s legal system reflects a progressive blend of historical, cultural, and jurisprudential factors, offering a gender-sensitive approach to Islamic legal reform. This study contributes to the broader discourse on contextual reinterpretation of Islamic law and encourages other Muslim countries to consider reforms aligned with the objectives of Sharia (maq??id al-shar?‘ah).